Yangpumicins F and G, Enediyne Congeners from Micromonospora yangpuensis DSM 45577 - Wang, Zilong (J Nat Prod, 2019)
Enediyne natural products are among the most cytotoxic small molecules and thus excellent payload candidates for the development of antibody-drug conjugates (ADCs). Here we report the isolation and structural elucidation of two new 10-membered anthraquinone-fused enediynes, yangpumicin (YPM) F (6) and G (7), together with five known congeners YPM A-E (1-5), from Micromonospora yangpuensis DSM 45577. YPM F (6) and G (7) showed strong cytotoxicity against the tested human cancer cell lines, as well as activity against several Gram-positive and Gram-negative pathogens. The 1,2-diols in 6 and 7 promise to enable new linker chemistry for the development of YPM-based ADCs.